2015
DOI: 10.1016/j.dsi.2014.12.008
|View full text |Cite
|
Sign up to set email alerts
|

A prospective clinical and histologic study of axillary osmidrosis treated with the microwave-based device

Abstract: a b s t r a c tBackground: Microwave-based devices target sweat glands through energy delivery at the dermal esubcutaneous interface. These devices have been approved by the Food and Drug Administration as a noninvasive treatment for axillary hyperhidrosis. Treatment for osmidrosis has only been reported in one preliminary study. Objectives: To investigate the efficacy, safety, and histological changes of the microwave-based devices in treating axillary osmidrosis. Methods: We conducted a prospective study in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 14 publications
2
17
0
Order By: Relevance
“…In our study, we found that microwave‐based therapy was effective in treating osmidrosis with minimal downtime, recurrence, and complications. Its efficacy in treating hyperhidrosis has been reported by a randomized controlled trial; studies have also reported its efficacy in treating osmidrosis . The long‐term follow‐up observations in our study indicate that microwave‐based therapy could be a durable and effective therapeutic modality for osmidrosis and is less operator‐dependent.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…In our study, we found that microwave‐based therapy was effective in treating osmidrosis with minimal downtime, recurrence, and complications. Its efficacy in treating hyperhidrosis has been reported by a randomized controlled trial; studies have also reported its efficacy in treating osmidrosis . The long‐term follow‐up observations in our study indicate that microwave‐based therapy could be a durable and effective therapeutic modality for osmidrosis and is less operator‐dependent.…”
Section: Discussionsupporting
confidence: 73%
“…This allowed for a higher level of microwave energy (level 5) to be applied, resulting in greater efficacy and preventing nerve injury . Furthermore, unlike conventional techniques reported in the literature, we carefully marked the alignment lines and treatment grids after tumescent anesthesia was infiltrated. If marking is performed before tumescent infiltration, tumescence‐induced skin distention, and line distortion may leave some areas untreated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Malodor brings negative psychological, social and family effects to patients (1)(2). It is often difficult for the conservative treatment to achieve satisfactory effects, while surgical removal of sweat glands has a definite effect (3)(4)(5)(6)(7)(8)(9)(10)(11). At present, sweat gland resection surgery mainly includes removal under direct vision and blind pruning and trimming with small incision.…”
Section: Introductionmentioning
confidence: 99%
“…However, for patients with blood coagulation disorders or undergoing surgery, dysfunctional coagulation causes bleeding or obstructive clotting 1 . Cryotherapy and radio frequency (RF) ablation are common solutions for therapy or vessel coagulation 2 3 4 5 6 . These treatment modalities induce a larger ablation area, resulting in extra damage to the surrounding tissue and difficulty with the treatment of specific areas or small vessels.…”
mentioning
confidence: 99%